Halal Lifestyle, Awareness, and Consumer Behavior: Implications for the Halal Food Market in Dayeuh Village, Indonesia - Oktapiani, Nurul; Al Farisi, Muhammad Salman; Herawati, Ermi (Jeksyah: Islamic Economics Journal, 2025)
This study aims to examine the influence of halal lifestyle and halal awareness on public purchase interest in halal food products. The research focuses on understanding how these factors contribute to consumer behavior in Dayeuh Village, Cileungsi District, Bogor Regency, West Java Province, Indonesia. A quantitative approach was employed, using a simple random sampling technique to select 100 respondents from the local population. Data were collected through questionnaires and analyzed statistically. The findings reveal that both halal lifestyle and halal awareness simultaneously have a significant and positive effect on public purchase interest. Consumers with a stronger understanding and commitment to halal principles tend to show greater interest in purchasing halal certified products. The study highlights that limited education about halal concepts remains a major barrier, which affects the level of public interest in halal consumption. Based on these findings, it is recommended that policymakers and stakeholders intensify educational programs and public awareness campaigns on the importance of halal lifestyles and certifications. Furthermore, collaboration between governmental institutions, halal certification bodies, and the food industry is essential to strengthen public knowledge and trust, thereby encouraging greater consumer engagement with halal products.